Rewriting difference : Luce Irigaray and "the Greeks" - Tzelepis, Elena; Athanasiou, Athena (SUNY series in gender theory., 2010)
In this definitive reader, prominent scholars reflect on how Luce Irigaray reads the classic discourse of Western metaphysics and also how she is read within and against this discourse. Her return to "the Greeks," through strategies of deconstructing, demythifying, reconstructing, and remythifying, is not a nostalgic return to the ideality of Hellenocentric antiquity, but rather an affirmatively critical revisiting of this ideality. Her persistent return and affective bond to ancient Greek logos, mythos, and tragedy sheds light on some of the most complex epistemological issues in contemporary theory, such as the workings of criticism, the language of politics and the politics of language, the possibility of social and symbolic transformation, the multiple mediations between metropolitan and postcolonial contexts of theory and practice, the question of the other, and the function of the feminine in Western metaphysics. With a foreword by Gayatri Chakravorty Spivak and a chapter by Irigaray responding to her commentators, this book is an essential text for those in social theory, comparative literature, or classics.